1975
DOI: 10.1007/bf00418975
|View full text |Cite
|
Sign up to set email alerts
|

Histologische und histomorphometrische Veränderungen bei Plattenosteosynthesen nach Osteotomien an der Tibia des Kaninchens

Abstract: In all specimens the cross-sections of bone taken at 4 marked points showed atrophy of the cortical bone which had occured in a typical manner. In the 1-week specimens no qualitative changes could be observed by normal light microscopy. In the 2nd week, however, a vivacious bone remodelling with wide Haversian canals and vessels starts from the medial cortex as could be seen identically in every series of our experiments. In the 4th week and especially in the 6th week it becomes also apparent on the lateral, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…The mineral loss was less profound than that reported by Gordes et al (1975b). This may be because mineral loss is greater in the plated osteotomized bone these authors studied than in plated intact bone.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The mineral loss was less profound than that reported by Gordes et al (1975b). This may be because mineral loss is greater in the plated osteotomized bone these authors studied than in plated intact bone.…”
Section: Discussioncontrasting
confidence: 53%
“…Gordes et al (1975b) observed that during the first 24 weeks after neutral rigid plate fixation of rabbit tibio-fibular bone cancellous transformation was progressive and profound. In our laboratory, the rigid plate fixation of intact rabbit tibio-fibular hone induced similar changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractures have been reported after removal of the plates (Richon et al 1967, Dietschi & Zenker 1973 Both adverse effects on bone tissue as a structure (Schenk & Willenegger 1967, Uhthoff & Dubuc 1971, Gordes et al 1975a, 1976 and reduction of the bone mineral mass 1974). (Gordes et al 1975b, Stromberg & Dalen 1976 have been reported in cortical hone after immobilization with a rigid plate.…”
mentioning
confidence: 99%
“…Cancellous transformation of both fractured and intact cortical bone has been observed following rigid plate fixation (6,11). Similarly external fixation and intramedullary nailing cause porotic transformation of the cortical bone (9,12), the extent of which seems to be less than after application of rigid plates.…”
mentioning
confidence: 99%